Xylocarpus granatum Mangrove Fruit Extract and Sodium Alginate Extract Lotion as Potent Wound Treatment Medicine - Delianis Pringgenies; Ervia Yudiati; Rini Widyadmi; Amelia C. Anggelina; Muhammad S. Bahry (Jurnal Biologi Papua, 2021)
A preliminary study to gauge the antimicrobial potency of Xylocarpus granatum mangrove fruit extract and sodium alginate extract against pathogenic microbe from the species Pseudomonas aeruginosa and Staphylococcus epidermidis. Lotions made of mangrove fruit extract (Sample 1) lotion and of a mixture of fruit extract and sodium alginate extract lotion (Sample 2) were topically tested on incision cut wound on mice abdominal area. The lotion was applied daily for five consecutive days. Observation on the test subjects were conducted to determine the rate of blood agglutination, tissue recovery rate, and fibroblast development rate using histology. The results showed that X. granatum extract lotion displayed significant antimicrobial activity against both pathogenic microbe species and did not show any conflict with the microbial activity found in sodium alginate lotion. Lotion adhesiveness test measured sample 1 at 0.26 seconds and sample two at 0.16 seconds. Both samples were shown to be oily in water. Subject observation showed blood coagulation on the first day, onset of tissue recovery on the second day and by the third day the wound had undergone complete tissue recovery. Observation on the fifth day showed that fibroblast tissue on the subject with sample 2 treatment was more solid than that with sample 1 treatment. It was concluded that the mix of X. granatum mangrove fruit and sodium alginate extracts showed most potency in wound treatment.Key words: X. granatum; incision wound; lotions; skin; histology; fibroblast.